Understanding the mechanism of action of denrophthoe pentandra leaves extract as anticancer agent - Sul'ain, Mohd Dasuki (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2016)
Throughout medical history, herbal plants have been shown to be one of valuable sources in combating cancer such as Dendrophthoe Pentandra (DP). However, the mechanism underlying anticancer activity is unclear and need to be explored. Therefore, DP was selected in order to evaluate its antiproliferative activity and mode of cell death in cancer treatment. The extraction of DP leaves were carried out using methanol as a solvent (DPME). Phytochemicals compound present in DPME were screened and quantified . Tannin is the most abundance phytochemical present in DPME. Further confirmation of its bioactive compound by Gas Chromatography - Mass Spectrophotometry (GC-MS) was done. Hexadecanoic acid, methyl ester (palmitic acid) and 9,12,15- octadecatrienoic acid, methyl ester (linolenic acid) were two compounds that probably contribute to antiproliferative property. The antiproliferative activities of DPME towards Hela, HepG2, MCF-7, U20S and MDA-MB-231 cell lines have been examined by MTI Assay and IC50 values were obtained. MCF-7 cells showed the most effective growth inhibition with lowest lC50 value upon treatment with DPME. The cytotoxicity activities towards normal kidney MDCK and normal connective L929 cells were evaluated to determine the cytoselectivity property of DPME. The nuclear staininq by Hoechst 33258 displayed the chromatin condensation, fragmented nuclei and formation of apoptotic bodies upon treatment with DPME according to certain period of time. Flowcytometric analysis using Annexin V/PI double staining has confirmed that DPME-treated MCF-7 arrested cell cycle distribution at G1/S phase and induced apoptosis. The mechanism of action was further confirmed by determination of protein involved in apoptosis pathway; Scl-2, Sax, p53 and cytochrome C. The results found out that the increased of p53 was followed by an increment of Sax, pro-apoptotic and decreased of Scl-2, anti-apoptotic. Activation of Sax and inactivation of Scl-2 triggered release of cytochrome C which leads to apoptosis event. In conclusion, DPME demonstrated antiproliferative activity in MCF-7 cells by induction of apoptosis. Therefore, it has a promising approach for breast cancer treatment. Other than DPME, Dendropthoe Pentandra Ethyl Acetate extract (DPEA) showed antiproliferative activity on MCF-7 of IC50 4.72±0.52 ~g/ml . From GC-MS analysis, DPEA also showed presence of decanoic acid, palmitic acid, linolenic acid and beta-sitosterol that might contribute to DP anticancer activity.